Produção de estímulos antecedentes à resposta de antecipar a posição final da bola de goleiros de handebol, na situação do tiro de sete metros - Lemos, Roberta Freitas (2008)
The objective of the current research was, in a seven-meter penalty, to identify and describe some peculiarities of looking and anticipating the final position of the ball emitted by goalkeepers, as well as the relationship between them. Four participants attended 264 filmed hurls from the goalkeeper s point of view, presented ramdomically in three sessions. Four different types of stimulus were produced: +1, completed in the first frame after the ball left the hand of the thrower; 0, completed in the last frame when the ball still was in the hand of the thrower; -1, completed one or two frames before type 0, and; -2, completed three or four frames before type 0. The participants were divided between two conditions: darkened screen', when, after the end of the scene, a 3 x 3 matrix was presented on a black screen, and paused image', when a 3 x 3 matrix was presented on the paused image of the last frame of the scene. The anticipating response consisted of pressuring the corresponding keyboard key to the quadrant where the ball had been hurled and was registered by the program that controlled the presentation. The looking response was registered by a tracking circuit of reflection cornea/pupil called Iscan®. In relation to the anticipation, all the participants with exception of participant C, anticipate more often the direction and height' of the ball than the direction' or `height' and the percentage of the anticipating response increases in face of more complete scenes. For the looking response, the arm seems to be the region where the eyes were located more often at the end of the hurls. For the participants who experienced the condition paused image' at the last moment before emitting the anticipating response, the distribution of the localizations of the look is larger in the different regions of the scene. Two standards were identified: the localization of the look predominantly in the same region and in a variation of nearby regions to distant regions of the body of the less-completed stimulus to most-completed one. For the relationships between the two responses, it is possible to observe that two participants emit a higher number of looking response in face of regions of the stimulus where, in the history of reinforcement, they achieved greater success, and the other two emit a higher number of replied to look in face of regions in which they achieved minor success